Girl forgotten - Henry, April (Christy Ottaviano Books/Little, Brown and Company, 2023)
When seventeen-year-old Piper Gray starts a true crime podcast investigating a seventeen-year-old murder cold case, she puts her life in danger as she digs deep into the mysteries of the past.